Maternal obesity influences Birth Weight more than gestational Diabetes author: - Eman M Alfadhli (BMC, 2021)
Abstract Background Maternal obesity and gestational diabetes (GDM) are commonly encountered during pregnancy. Both conditions are independently associated with unfavorable pregnancy consequences. The objective of this study was to compare the effects of obesity and GDM on birth weight, macrosomia, and other adverse pregnancy outcomes. Methods This cohort study involved 531 women with a singleton pregnancy attending the Maternity and Children's Hospital, Medina, Saudi Arabia, between June 2014 and June 2015. Participants underwent a 75-g oral glucose tolerance test between 24 and 28 weeks. The International Association of Diabetes and Pregnancy Study Groups criteria were used for GDM diagnosis. BMI was assessed at the first antenatal visit, and obesity was defined as a BMI ≥30.0 kg/m2. All women were followed up until delivery. Women were divided into 4 groups: non-GDM nonobese (reference group), GDM nonobese, obese non-GDM, and obese GDM. Clinical characteristics and adverse pregnancy outcomes were compared. Results The mean age and BMI of the participants were 30.5 years and 29.3 kg/m2, respectively. GDM was diagnosed in 50.2% of the participants, and obesity was diagnosed in 47.8% of the participants. Obese women with GDM were the oldest and heaviest among all women. The mean birth weight increased in order among the four groups; it was highest in the infants in the obese GDM group, followed by those in the obese non-GDM, GDM nonobese and reference groups. Obesity and GDM alone or in combination were associated with higher rates of macrosomia and cesarean deliveries than the reference group. Neonatal intensive care unit (NICU) admission was higher in infants in the GDM nonobese and obese GDM groups. The frequency of low Apgar score was significantly higher in infants in the obese GDM group than in infants in the reference group. Conclusions Maternal obesity seems to influence birth weight more than GDM, while GDM is associated with a greater risk of admission to the NICU. The combination of both conditions is associated with the greatest risk of adverse pregnancy outcomes.